1994
DOI: 10.2172/10102976
|View full text |Cite
|
Sign up to set email alerts
|

Waste tank vapor project: Vapor characterization of Tank 241-C-103: Data report for OVS samples collected from Sample Job 7b, Parts I and II, received 5/18/94 and 5/24/94

Abstract: Portions of this document may be illegible in electronic image products. Images are produced from the best available original document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The semivolatile alkane results shown in Table 4-33 are those of Jenkins et al (1994), Clauss et al (1994), and Ligotke et al (1994a). These alkanes are the major components of NPH.…”
Section: -39supporting
confidence: 59%
See 1 more Smart Citation
“…The semivolatile alkane results shown in Table 4-33 are those of Jenkins et al (1994), Clauss et al (1994), and Ligotke et al (1994a). These alkanes are the major components of NPH.…”
Section: -39supporting
confidence: 59%
“…Deuterated ndcdecane and n-bidecane spiked OSHA versatile sampler (OVS) trap samples were analyzed blr Clauss et al (1994), who concluded matrix effects were not significant.…”
Section: 425mentioning
confidence: 99%
“…If sampling efficiency is high, the first section of sorbent media collects nearly "allof analyte, and the second section (the breakthrough section) collects very little analyte. Analysis of breakthrough sections are discussed by Ligotke et al 1994, andClauss et al 1994. All sample job 7B sorbent trap samples were collected using the VSS. The sorbent trap station of the VSS allows collection of two sorbent traps simultaneously, and most samples were taken in pairs.…”
Section: Sorbent Trap Samplesmentioning
confidence: 99%
“…Deuterated dodecane, for example, served as a surrogate spike for dodecane in OVS trap sampling. All TSTs (and certain OVS traps) were spiked with surrogate compounds not exIx_ted to be found in tank 241-C-103 (e.g., deuterated bromobenzene) in known quantifies before being used to collect samples (Jenkins et al 1994, Clauss et al 1994. Desorption efficiency is calculated by comparing the amount of surrogate recovered with the amount spiked.…”
Section: Whc-ep-0780mentioning
confidence: 99%
See 1 more Smart Citation